Workshop Implementasi Kurikulum Merdeka Belajar di SMAK Loli Timor Tengah Selatan - Afi, Kristian E Y M; Nggeong, Fransiska Y; Baun, Nofriana; Tefa, Sriyanti; Dethan, Yandry Diana (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Abstract. Loli Christian High School, located in South Central Timor Regency, East Nusa Tenggara Province, is one of the private senior high schools that has not implemented the Merdeka curriculum in its learning. Therefore, this community service activity (PKM) aims to introduce the independent curriculum so that teachers can implement it little by little in their lesson document. This activity applied lecturing method in socializing the independent curriculum (the policy of implementing the independence curriculum and the preparation of the Education Unit Operational Curriculum (KOSP) and organizing learning in accordance with the school’s vision, mission, and goals) and training methods in training the making of teaching materials. Participants in this activity are the 22 teachers in Loli Christian High School. Assignment of Memorandum of Understanding (MoU) was also held in this community service activity. This activity received a very good response from school which could be seen from the enthusiasm of all participants in all activities carried out for two days by the PKM team.